MAKNA SYAIR ASYROQOL PADA TRADISI SERAKALAN DIACAR PESTA PERNIKAHAN - yarso, Varulian; Ismunandar, Ismunandar; Muniir, Asfar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research analyzing about Meaning of lyrics the Serakalan in Sungai Jaga B village at Sungai Raya sub-district, Bengkayang District. The problem of research in this research is 1). Meaning of the lyrics the Serakalan in Sungai Jaga B village at Sungai Raya sub-district, Bengkayang District. 2). How were implementation of result the research done the Meaning of the lyrics to the Serakalan for learning in the school. This research used descriptive methods and a research reom used was qualitative research. In this research used sosiology approach. The source of data in this research is Darmawan and Muaiyat. The data in this research is interview results, observation results, sound recording, notebook, foto and video about Meaning of lyrics the serakalan at Sungai Jaga B village in Sungai Raya sub-district, Bengkayang District. Data collection techniques such as observation, interviews, and documentation. Technique to test the validity of data used was source an extension of observatioin and data analysis tecniques. The result of this study is lyrics of serakalan, lyrics navigate is Asyroqol. Meaning of lyrics Asyroqol is worshiped for Nabi Muhamad Saw, excrescent Nabi Muhamad Saw, and praise Nabi Muhamad Saw. perfomance (the presentation will be sempa mask, betel leaf, areca nut and others). This result implementation as learning meterials about meaning of lyrics Serakalan, teach about understanding meaning of lyrics Serakalan in class eight grade, first semester, in 2013 curriculum.Â Key word : Meaning Of Lyrics, Serakalan